Resonant cavity-enhanced quantum dot field-effect transistor as a single-photon detector - 董宇 王广龙 王红培 倪海桥 陈建辉 高凤岐 乔中涛 杨晓红 牛智川 (Chinese physics B, 2014)
A resonant cavity-enhanced （RCE） quantum dot （QD） field-effect transistor （RCEQDFET） is designed for single- photon detection in this paper. Adding distributed Bragg reflection （DBR） mirrors to the single-photon detector （SPD）, we improve the light absorption efficiency of the SPD. The effects of the reflectivity of the mirrors, the thickness and light absorption coefficient of the absorbing layer on the detector＇s light absorption efficiency are investigated, and the resonant cavity is determined by using the air/semiconductor interface as the mirror on the top. Through analyzing the relationship between the refractive index of AlxGal_xAs and A1 component, we choose A1As/Alo.15Gao.85As as the material of the mirror on the bottom. The pairs of A1As/Alo.15Gao.85As film are further determined to be 21 by calculating the reflectivity of the mirror. The detector is fabricated from semiconductor heterostructures grown by molecular beam epitaxy. The reflection spectrum, photoluminescence （PL） spectrum, photocurrent response, and channel current of the detector are tested and the results show that the RCEQDFET-SPD designed in this paper has better performances in photonic response and wavelength selection.